Emerging Roles of microRNAs in Ischemic Stroke: As Possible Therapeutic Agents - Khoshnam, Seyed Esmaeil; Winlow, William; Farbood, Yaghoob; Moghaddam, Hadi Fathi; Farzaneh, Maryam (Journal of stroke, 2017)
Stroke is one of the leading causes of death and physical disability worldwide. The consequences of stroke injuries are profound and persistent, causing in considerable burden to both the individual patient and society. Current treatments for ischemic stroke injuries have proved inadequate, partly owing to an incomplete understanding of the cellular and molecular changes that occur following ischemic stroke. MicroRNAs (miRNA) are endogenously expressed RNA molecules that function to inhibit mRNA translation and have key roles in the pathophysiological processes contributing to ischemic stroke injuries. Potential therapeutic areas to compensate these pathogenic processes include promoting angiogenesis, neurogenesis and neuroprotection. Several miRNAs, and their target genes, are recognized to be involved in these recoveries and repair mechanisms. The capacity of miRNAs to simultaneously regulate several target genes underlies their unique importance in ischemic stroke therapeutics. In this Review, we focus on the role of miRNAs as potential diagnostic and prognostic biomarkers, as well as promising therapeutic agents in cerebral ischemic stroke.